The knight's rebellious maiden - Matthews, Ella (Harlequin historicals., 2024)
He’s her protector. She’s his forbidden temptation! Sir Leopold’s first mission is supposed to be a chance to prove his valor. But tasked with safely escorting Lady Arianwen to her husband-to-be, Leo finds he is little but a glorified bodyguard. Only, the seemingly simple mission goes awry when Ari proves that she’s willing to do anything to get away from her impending nuptials. As attraction sparks between them, can Leo choose knightly duty over love and deliver Ari to her wedding?